Oppression of General IDI Amin Dada in Ruling People (Objective) - Suswanto Ismadi Megah (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
This study analyzed the ruling of the Idi Amin Dada. This used to identify how he oppressed his people cruelly. This study applied Marxist theory by Karl Marx and social class by Lewis. In addition, this study also explained how the new independent country ruled by the military system. Marxist Theory and social class theory analyzed the class onflict between the strong and the weak people. Status in social analysis and in practice, the notion of social class The dictatorships of his government made thousands people killed. This study applied qualitative research method. The data obtained from the scene and script of the rise and Fall Idi Amin Movie. The result of the study that the oppression occurred during his ruling country. The oppressions were he oppressed his people by his power. His soldiers who oppressed civil cruelly. Then the oppression occurred between man and women, this reflected General Idi Amin and his wives. The last was he oppressed the foreigners to get out of Uganda. Keywords : oppression, ruling and idi Amin